Outcomes of critically ill adult patients with continuous renal replacement therapy-requiring acute kidney injury in the Free State province of South Africa: the impact of HIV - Camara, Seydou Nourou; Chothia, Mogamat-Yazied (African Journal of Nephrology, 2017)
Background: Continuous renal replacement therapy (CRRT)-requiring acute kidney injury (AKI) in critically ill adult patients frequently occurs in the intensive care unit and is associated with high morbidity and mortality. There is a paucity of epidemiological data regarding CRRT-requiring AKI in sub-Saharan Africa. Methods: We conducted a retrospective cohort study of all critically ill adult patients with CRRT-requiring AKI at Universitas Academic Hospital, Bloemfontein, during the period 1 July 2010 to 30 June 2014. The primary purpose was to determine the incidence of CRRT-requiring AKI. Secondary objectives were to record mortality, renal recovery and duration of CRRT. Results: The number of patients with CRRT-requiring AKI was 87 (1.1%) of the 7 709 patients admitted to the ICU over this 4-year period. Of these, 37 (43%) were HIV infected. The median age was 56 years (43 years in the HIV-infected versus 64 years in the HIV-uninfected group (P < 0.01). The majority of the HIV-infected patients were Black (89%). Metabolic acidosis together with pulmonary oedema and oliguria were the main indications for dialysis. The overall mortality was 31% with most of the deaths (82%) occurring in the HIV-positive patients. These patients had a mortality rate of 60% versus 10% among the uninfected (P < 0.01. Multivariate logistic regression identified female sex and HIV infection as independent predictors of mortality. The median duration of CRRT was 3 days and renal recovery occurred in 26% of patients. Conclusions: The incidence of CRRT-requiring AKI in critically ill adult patients at Universitas Academic Hospital was low. The overall mortality was relatively low when compared to that reported by others; however, it was relatively very high in the HIV-infected group.